Nonsurgical treatment of adult acquired flatfoot is effective: A narrative review - Abhishek Vaish; Jyoti Sitaula; Raju Vaishya (Apollo Medicine)
Adult acquired flatfoot is a common clinical condition having complex pathology-posterior tibial tendon insufficiency and failure of ligamentous and capsular structures of the foot. There still remains a controversy in the management algorithm of the flexible flat foot. Conservative management is considered as the initial treatment, surgery being offered only when the conservative measures fail. The paramount importance is to assess the functional outcomes of conservative treatment, as not enough publications exist to evaluate its importance. This study aims to analyze evidence of benefits with nonsurgical treatment of the adult acquired flat foot. Online databases such as PubMed, Google Scholar, and Scopus were systematically searched for nonsurgical treatment of adult acquired flat foot in November 2019. Keywords used were “Flatfoot,” “Adult,” and “Pes planus.” The Boolean operators used were (AND), (OR), and (NOT). Five studies that matched our criteria were analyzed to assess the nonoperative treatment of adult flat foot for this review. Patient satisfaction with nonoperative treatment ranged from 60.6% to 89%. Conservative treatment was successful in 83%–87.5% and only the remaining patients required surgery. All of these studies support the use of a conservative approach in the management of acquired flatfoot deformity in adults in the form of orthotics with or without physiotherapy. Conservative methods are the mainstay of the management for Stage I and II AAFFF (Adult Acquired Flexible Flat Foot) with satisfactory functional results. The patient education and a reasonable period of care are essential for good outcomes. Surgery is necessary for patients in whom conservative management has failed and in all patients with fixed deformities.